New technologies, continuing ideologies: Online reader comments as a support for media perspectives of minority religions. (August 2018) - Bruce, Tayyiba
Highlights: Right-leaning news websites typically represented Islam and Catholicism through stereotypes. Overlap in semantic categories indicated shared ideologies of news and audience in this context. Keywords reflected collectivisation of communities and nationalistic statements in comments. Dominant ideologies supported in these websites, despite shifts in media technologies. Some evidence for resistance to dominant ideology was highlighted in comments. Abstract: The recent growth of populism has resulted in dramatic political change in British, European and American politics. Given the role of right-wing media in legitimising and encouraging traditionalist, nationalist or sometimes far-right populist discourse, the linguistic and semantic relationship between news and readers' discourse in the context of right-leaning news websites merits investigation in the current climate. This paper examines the relationship in terms of representations of Islam and Catholicism in Daily Mail and Telegraph websites. Empirical keyword analysis of news articles and linked comments is presented. Key semantic categories revealed evidence for stereotypical representation of these religions, as applicable to new media contexts and enacted in the websites of traditional print media. Results highlighted that long-term themes such as 'Islamic terrorism, war and extreme belief' and 'the Pope, Vatican and scandals in the Catholic Church' continue to dominate news stories online. 18 out of 19 categories in Islam news repeated in comments, and 9 out of 13 in Catholicism news repeated in comments. This strong overlap indicated close connections between news and comments and shared ideologies. Higher numbers of semantic categories in comments showed greater variation of topics than news, with 15 and 23 additional categories in Islam and Catholicism comments respectively. However, key multi-words reflecting collectivisation of communities, such as Muslim country, were identified in news and repeated in comments. Investigation of Muslim country revealed nationalistic and polarising statements by readers, while investigation of penitents revealed portrayal of Catholics as an 'out-group' through lexis which denoted violence, shock and crime. Closer analysis of some keywords revealed polarity between readers displaying differing views in relation to various aspects of religion. Taken together, however, findings suggested that age old stereotypes of minority religions were perpetuated in new media contexts.